Tratamiento post-quirúrgico a pacientes de cirugía bariátrica - Calvopiña Ponce, Diego Alexis (2023)
abstrac obesity is a real global health problem. it conditions the presence of other diseases, generating high rates of disability and affecting the perception of quality of life related to health. bariatric surgery constitutes a therapeutic alternative to the treatment of obesity with favorable results in its use. the objective of this research was to carry out a non-systematic bibliographic review to describe the adequate post-surgical management in patients with bariatric surgery. a total of 82 documents were identified, of which 45 were used in the study. the information was obtained from regional (latindex, lilacs, scielo, and redalyc) and high-impact databases (scopus, medline, pubmed, and ice web of science). the main results include the description of the general elements that relate obesity with other non-communicable chronic diseases, such as diabetes mellitus; the general elements related to bariatric surgery were also described with emphasis on the benefits, advantages, indications and complications of the surgical procedure, as well as the post-surgical follow-up of patients who underwent bariatric surgery, for which a follow-up algorithm was designed. of these patients. it is concluded that bariatric surgery provides indisputable advantages in the treatment of obesity; however, it is not exempt from presenting immediate, mediate and late complications, so the follow-up of the patient subjected to this procedure must be carried out systematically to detect the presence of these complications early. keywords: bariatric surgery; metabolic surgery; diagnostic management; therapeutic management